Analisis Manajemen Strategi BAZNAS Kota Ambon - Tangke, Diar Muzna (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2020)
Zakat has a very strategic role in efforts to reduce poverty or economic development. In the management of zakat, it is necessary to create a strategy so that there is a formula as a reference in its management. This study aims to determine strategic management in the management of Baznas Ambon City. The research method used is a qualitative method with analysis tools, namely SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). From the results of organization profile analysis and environmental analysis, it is known that the strengths, weaknesses, opportunities, and threats (threads) of Baznas City. Baznas Ambon has a weakness in the form of not optimal socialization. There is no mustahik database, the office is not permanent (leased), the lack of support from UPZ as an extension of the Baznas Ambon City, lack of training and technical skills for Baznas management apparatus. By maximizing strength from the internal side and opportunities from the external side and utilizing the large potential of zakat, Baznas Ambon City can become an institution that the public can trust.